PELAKSANAAN PEMENUHAN HAK BURUH PASCA PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI PEKANBARU - Reza, Muhammad Jourdy; Firdaus, Firdaus; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The Industrial Relations Court is a special court established within thedistrict court which has the authority to examine, adjudicate and make decisionson industrial relations disputes, this is stated in Article 1 paragraph 17 of LawNumber 4 of 2004 concerning Settlement of Industrial Relations Disputes.according to Article 97 of Law Number 2 of 2004 concerning Settlement ofIndustrial Relations Disputes, the decision of the Industrial Relations Courtdetermines the obligations that must be carried out and/or the rights that must beaccepted by the parties or one of the parties for any settlement of industrialrelations disputes. However, the implementation did not run smoothly whichresulted in legal uncertainty and the failure to fulfill the rights of laborers oremployees guaranteed by Article 156 paragraph 1 of Law Number 13 of 2003concerning Employment which states "In the event of termination of employment,employers are required to pay severance pay and/or service award money andcompensation money for rights that should have been received."The type of research used is empirical legal research. Empirical legalresearch is a legal research method that functions to be able to see the law in realterms and examine how the law works in a social environment, so the empiricallegal research method can also be said to be sociological legal research.This research discusses the implementation of the fulfillment of laborrights after the decision of the Industrial Relations Court at the PekanbaruDistrict Court. The results showed that the implementation of the fulfillment oflabor rights has been carried out well, although there are still some obstaclessuch as delays in submitting requests for execution by workers, delays inexecution by companies, lack of ability of workers in tracking company assets,and efforts by companies to cover up their assets. However, the PekanbaruDistrict Court has made preventive and repressive efforts to overcome theseobstacles, including by summoning both parties when giving a warning to thecompany, directing workers in tracking assets, and providing cover letters torelevant agencies in the asset confiscation process.Keywords: Industrial Relations, Labor Rights, Implementation.